Hubungan Tingkat Keparahan (Grading) Penyakit Katarak Senilis dengan Tingkat Depresi pada Lansia - Siyamto, Siyamto; Indrajanti, Mirza; Goenawan, Kristian; Silaen, Desi Hartati (Universitas Kristen Krida Wacana, 2026)
The aging population in Indonesia accompanied by a demographic dividend has caused an increase in the elderly population. The aging process can usually be accompanied by a decrease in visual sensory disorders with senile cataracts. The presence of senile cataracts can cause depressive disorders that have an impact on the mental health of the elderly. Purpose to determine the relationship between the severity (grading) of senile cataract disease with the level of depression in diagnosis of senile cataracts patiens at the UKRIDA Hospital in Jakarta. Method is a correlational analysis study using primary and secondary data from patients with a diagnosis of senile cataracts with an accidental sampling technique. Data analysis using the Gamma Correlation test. The study with 72 patient sample and found an average age of 68 years with grade 1 senile cataract disorders of 44 people (61.1%). Patients with senile cataracts with mild depressive disorders of 41 people (56.9%) Conclusions are the correlation between the severity (grading) of senile cataracts and the level of depression in elderly patients is not significant or does not have a significant relationship with a p-value 0,400. A correlation value of 0,200 indicates a positive correlation with a very weak and meaningless correlation strength.